Morphometric characteristics of Lake Limboto as critical lake in Gorontalo Province, Indonesia - YUNGINGER, RAGHEL; PATUTI, INDRIATI MARTHA; SUPU, IDAWATI; GAFUR, NURFITRI ABDUL; ZULKIFLI, MUHAMMAD; HASAN, ELFIRAWATI; MASRURAH, ZAKIA; ZULAIKAH, SITI; TISEN, TISEN (Jurnal Natural, 2024)
This research aims to investigate the factors leading to siltation in Lake Limboto by analyzing its morphometric characteristics gathered through direct field measurements and remote sensing using Geographic Information System (GIS). Lake Limboto covers an approximate surface area of 26.09 square kilometers, boasts a maximum depth of 4 meters, and maintains an average depth of 2.83 meters. The Shoreline Development Index (SDI) stands at approximately 2.57, indicating an irregular shape of the lake's water body, while the Lake Volume Development (VD) index, at 2.12, suggests a generally flat lake bottom. The Relative Depth (Zr) registers at around 0.69%, as observed from the water turbidity level. The lakebed relief in the vicinity of the lake's periphery is predominantly flat and shallow, particularly in the western, northern, and southern regions, with depths measuring less than 2 meters. In contrast, the lakebed relief in the central and eastern sections tends to be less flat but still features depths of less than 4 meters. Siltation in Lake Limboto primarily results from high sediment input originating from erosion processes, agricultural activities, and settlements in the surrounding area.